101 Medicare Expenditures for Elderly Patients Undergoing Surgical Clipping or Endovascular Intervention for Subarachnoid Hemorrhage. (1st August 2016) - Bekelis, Kimon; Gottlieb, Dan; MacKenzie, Todd; Lanzino, Giuseppe; Lawton, Michael T.; Tjoumakaris, Stavropoula I.; Jabbour, Pascal
Abstract: INTRODUCTION: The impact of treatment method (surgical clipping or endovascular coiling) on the cost of care of patients with aneurysmal subarachnoid hemorrhage (SAH) is debated. We investigated the association of treatment method with long-term Medicare expenditures in elderly patients with aneurysmal SAH. METHODS: We performed a cohort study of 100% of Medicare fee-for-service claims data for elderly patients, who underwent treatment for ruptured cerebral aneurysms from 2007 to 2012. In order to control for measured confounding, we used propensity score-adjusted multivariable regression analysis with mixed effects to account for clustering at the hospital referral region level. An instrumental variable (regional rates of coiling) analysis was used to control for unmeasured confounding by creating pseudo-randomization on the treatment method. RESULTS: During the study period, there were 3210 patients, who underwent treatment for ruptured cerebral aneurysms, and met the inclusion criteria. Of these, 1206 (37.6%) had surgical clipping, and 2004 (62.4%) had endovascular coiling. The median total Medicare expenditures in the first year after admission for SAH were $113 000 (interquartile range $77 500-$182 000) for surgical clipping, and $103 000 (interquartile range $72 900-$159 000) for endovascular coiling. When we adjusted for unmeasured confounders, using an instrumental variable analysis, clipping was associated with increased 1-year Medicare expenditures by $19 577 (95% confidence interval, $4492-$34 663). CONCLUSION: In a cohort of Medicare patients with aneurysmal SAH, after controlling for unmeasured confounding, we demonstrated that surgical clipping was associated with increased 1-year expenditures in comparison with endovascular coiling.